The Role of Necroptosis in Burn Injury Progression in a Rat Comb Burn Model. (16th September 2015) - Reddy, Avanish S.; Abraham, Ariel; McClain, Steve A.; Clark, Richard A.F.; Ralen, Pryanka; Sandoval, Steven; Singer, Adam J.; Zehtabchi, Shahriar
Abstract Objectives Progression of cell death after burn injury may occur by one of three mechanisms: passive necrosis, apoptosis, and programmed necroptosis that requires the receptor‐interacting protein kinase‐3 (RIP‐3). The hypothesis was that RIP‐3 is present in normal and burned skin; that necroptosis plays a role in burn injury progression; and that treatment with necrostatin‐1, an inhibitor of necroptosis, would reduce burn progression. Methods Skin specimens from rats were examined for the presence of RIP‐3. Using a 150‐g brass comb preheated to 100°C, we created two comb burns (one on each side) consisting of four rectangular burns, separated by three unburned interspaces, on both sides of the backs of anesthetized male Sprague‐Dawley rats (240 to 300 g). The interspaces represent the ischemic zones surrounding the central necrotic core. Left untreated, these areas undergo necrosis. In the first experiment, 10 rats each were randomized to 1.65 mg/kg necrostatin‐1 or control given by intraperitoneal injection 1 hour after injury. In the second experiment, 10 rats each were randomized to two intravenous injections of 1.65 mg/kg necrostatin‐1 or its vehicle at 1 and 4 hours after injury. The primary outcome was the percentage of interspaces undergoing necrosis within 7 days of injury. Binary data were compared with chi‐square or Fishers' exact tests. Results All normal and burned skin specimens from rats stained positive for RIP‐3. In the first experiment, nearly all unburned interspaces in both the experimental and the control rats underwent necrosis (47 of 48, 97.9% vs. 48 of 48, 100%; p = not significant [NS]). Similarly, in the second experiment, there was no difference in the percentage of unburned interspaces undergoing necrosis within 7 days of injury in rats treated with two doses of necrostatin‐1 or the control vehicle (46 of 48, 95.8% vs. 48 of 48, 100%; p = NS). There were no wound infections noted in rats injected with necrostatin‐1. Conclusions The skin of rats contains RIP‐3 necessary for necroptosis. Injection of rats with either a single intraperitoneal dose or two intravenous doses of necrostatin‐1 failed to reduce burn injury progression in a rat comb burn model. This may be due to inactivity of necrostatin‐1 or the lack of a role of necroptosis in burn injury progression in the rat comb burn model.